Fatty liver index predicts further metabolic deteriorations in women with previous gestational diabetes. - Latife Bozkurt (Public Library of Science (PLoS), 2012)
Background and aims Determinants of fatty liver (FL) might be predictive for further deterioration in insulin resistance (IR) in women with previous gestational diabetes (pGDM). The aim was to evaluate the association between pGDM, FL and future manifestation of type 2 diabetes (T2DM) by a detailed pathophysiological characterization early after pregnancy. Methods 68 pGDM and 29 healthy controls were included 3-6 months after delivery and underwent specific metabolic assessments: status of IR was determined via oral- and intravenous-glucose-tolerance-tests with analysis of proinflammatory factors and kinetics of free-fatty-acids (FFA). According to the fatty-liver-index (FLI), pGDMs were categorized into three groups with low (FLI≤20), intermediate (20<FLI<60) and high (FLI≥60) risk for FL to assess differences in metabolic parameters at baseline as well as in the 10-year incidence for T2DM. Accuracy of FLI was proven with 1H-magnetic-resonance-spectroscopy. Results FL was strongly associated with IR in pGDM. pGDM with FLI≥60 showed significantly increased interleukin-6, plasminogen-activator-inhibitor-1, tissue-plasminogen-activator, fibrinogen and increased ultrasensitive-C-reactive-protein compared to the low risk group (FLI≤20). Analysis of FFA indicated a less pronounced decrease of plasma FFA levels during the oral-glucose-tolerance-test in subjects with FLI≥60. History of GDM plus FLI≥60 conferred a high risk for the manifestation of diabetes over 10 years of observation as compared to pGDMs with FLI≤20 (HR:7.85, Cl:2.02-30.5, p = 0.003). Conclusion FL is closely linked to GDM, especially to IR and inflammation. Most interestingly, subjects with the highest FLI values showed significant alterations in FFA kinetics and a higher risk to develop T2DM in future.